Development of Environmental – Student Behaviour Production Rules Scheme for the Internet of Things (IoT) Indoor Air Quality (IAQ) Data Reasoning - A., Nor Azhar; M., Rahmah; A. H, Roslina; Z., Fauziah (Universiti Malaysia Pahang, 2020)
The behaviour of students in a classroom is hardly being recognised by the instructor. A recent development, a researcher determines these traits by using a permissive approach. In this paper, a real-time classroom environment using a sensing device with detection of student behaviour is proposed. Recent studies as guidelines for this paper lead to three early hypotheses; development of the engine to detect student’s behaviour based on environmental sensing, faster production rules and reliability using economic sensors. The production rules are created step by step based on expert endorsements in three different areas; environmental, health, and education. The testbeds are three classrooms with separate periods had been deployed to proof the hypothesis. The result shows a promising output, which is all hypotheses are entirely accepted.